Enzymatic detection of mercuric ions in ground-water from vegetable wastes by immobilizing pumpkin (Cucumis melo) urease in calcium alginate beads - Prakash O.; Talat M.; Hasan S.H.; Pandey R.K. (My University, 2025)
Present report describes a quick and simple test based on enzyme inhibition for the detection of mercury in aqueous medium by urease immobilized in alginate beads. Urease was extracted from the discarded seeds of pumpkin (Cucumis melo) and was purified to apparent homogeneity (5.2-fold) by heat treatment at 48 ± 0.1 °C and gel filtration through Sephadex G-200. The homogeneous enzyme preparation (Sp activity 353 U/mg protein, A280/A260 = 1.12) was immobilized in 3.5% alginate leading to 86% immobilization. Effect of mercuric ion on the activity of soluble as well as immobilized enzyme was investigated. Hg2+ exhibited a concentration-dependent inhibition both in the presence and absence of the substrate. The alginate immobilized enzyme showed less inhibition. There was no leaching of the enzyme over a period of 15 days at 4 °C. The inhibition was non-competitive and the Ki was found to be 1.26 × 10-1 μM. Time-dependent interaction of urease with Hg2+ exhibited a biphasic inhibition behavior in which approximately half of the initial activity was lost rapidly (within 10 min) and reminder in a slow phase. Binding of Hg2+ with the enzyme was largely irreversible, as the activity could not be restored by dialysis. The significance of the observations is discussed. © 2007 Elsevier Ltd. All rights reserved.